Pemberdayaan Pengrajin Perempuan Penenun Sarung ATBM (Alat Tenun Bukan Mesin) - Farida, Farida; Christantyawati, Nevrettia (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
Community empowerment through MSMEs is now a central theme that is often raised by some researchers and also a major concern for the government, especially by the Office of Cooperatives and Small and Medium Micro Enterprises. Data released by the Office of Cooperatives and SMEs in 2013, the contribution of cooperatives and SMEs reached more than Rp 600 trillion or about 57% of East Java GDP that reached Rp 1.012 trillion. Besides, the industry of 54.34% in East Java also comes from MSME which can accommodate 98% of the workforce (Bappeda Jtim, 2014). Year 2015 is currently promoting OVOP (One Village One Product). This is the government's way of improving products coming from the region. Sambopinggir and Cerme is a small area in Lamongan and Gresik regency producing weaving ATBM sarong. A group of women weavers of ATBM sarong weavers are a small part of a group of women who take part in a small business of hand-made crafts that are purely human-dependent. Currently weaving fabric manufacturer products that many appear in the market of course very worrying and means of business continuity in the future. Prices for cheaper factory sarongs and varied designs will make ATBM woven sarongs to be lost far away. This is where the need for various parties to keep preserving hand-weaving business that has been running this year-long so as not to become extinct. In this program a group of women weavers weavers will be trained on the design of the woven sarong products to be more varied, the processing of cloth sarong weaving into other forms such as bags, mukena and clothes so more selling effects as well as packaging and product naming. Marketing is also no longer done conventionally so that ATBM woven sarong products can be marketed more widely. Keywords: group of women weavers, ATBM weaving sarong